2017
DOI: 10.1080/10872981.2017.1368849
|View full text |Cite
|
Sign up to set email alerts
|

Research productivity of doctor of physical therapy faculty promoted in the southeastern United States

Abstract: Background: Little information exists on the research productivity of successfully promoted tenure-track Doctor of Physical Therapy (DPT) faculty. Objective: To determine the research productivity that typically results in successful promotion. Design: We collected publicly available curriculum vitae (CVs) from faculty currently in accredited DPT programs and who had been successfully promoted from an institution in the southeastern USA from 2000 through 2016.Total publication count, journal impact factor, fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 12 publications
3
5
0
Order By: Relevance
“…In this study, publicly available curriculum vitae harvested directly from institutional faculty web pages were used to collect data on faculty research productivity. This method has been used previously in the literature (Barnard-Brak et al 2011), and has been found to be consistent with data obtained through self-reporting surveys (Kaufman 2009;Littman et al 2017;Holcomb et al 1990). In order to distinguish barriers to academic research productivity surrounding economic factors related to institutional location, this study uses the regional breakdown of the United States as defined by the Bureau of Economic Analysis which specifically identifies regional variations in production, personal income, and real property assets.…”
Section: Introductionsupporting
confidence: 53%
See 4 more Smart Citations
“…In this study, publicly available curriculum vitae harvested directly from institutional faculty web pages were used to collect data on faculty research productivity. This method has been used previously in the literature (Barnard-Brak et al 2011), and has been found to be consistent with data obtained through self-reporting surveys (Kaufman 2009;Littman et al 2017;Holcomb et al 1990). In order to distinguish barriers to academic research productivity surrounding economic factors related to institutional location, this study uses the regional breakdown of the United States as defined by the Bureau of Economic Analysis which specifically identifies regional variations in production, personal income, and real property assets.…”
Section: Introductionsupporting
confidence: 53%
“…The data is reported here in a style similar to that published previously (Littman et al 2017) in order to aid in direct comparison between the regions. As described in Table 1, the median publication count for DPT faculty promoted from Assistant to Associate Professor in the Western region was 3 with an average of 5.4 (5.5) with a range of 0 to 18 publications.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations